REHABILITACJARehabilitation in patients with HeartWare left ventricular support devices - Oleszczyk, Krystian; Zielińska-Meus, Anna; Pacholewicz, Jerzy; Zielińska, Teresa; Bolewska-Leszczyńska, Bożena; Rybicki, Jerzy; Sykosz, Teresa; Bugajska-Sysiak, Katarzyna; Staroszczyk-Głąb, Weronika; Kurek, Barbara; Szeląg, Anna; Gutkowska, Aurelia; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction : Cardiac transplantation is associated with high survival rates in patients with end-stage heart failure but the organ supply is limited. Implantable ventricular assist devices are one of end-stage heart failure treatment methods. They are used as a bridge to transplantation, a bridge to recovery of heart to have time for cardiac regeneration and also as a destination therapy Aim of the study : The aim of this study was to assess the second stage of rehabilitation in patients with implantable left ventricular heart devices of the HeartWare type. Material and methods : 4 patients aged 38, 47, 62 and 63 years underwent a cardiac rehabilitation program: physical exercises and psychotherapy 3 months after implantation of HeartWare devices. A 6-minute walking test was used to assess the results before and after rehabilitation. Aerobic exercises, resistance training, stationary bicycle training and psychotherapy were used during rehabilitation. Results : Exercise tolerance and psychological state were improved after rehabilitation.